PERAN PENDAMPINGAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MELALUI KOMUNITAS BELAJAR DI SDN KALONGAN 01 - Apriliya, Nurul; Kurniawan, Matius; Soedjono, Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The government, through the Ministry of Education and Culture, has implemented the Independent Curriculum (KurMer) for kindergarten, elementary, middle school, vocational school and high school levels. One of the components needed for the successful implementation of an independent curriculum is the availability of competent educators. Improving student learning outcomes depends on the competence of educators, so a school principal must be able to facilitate increasing the competence of educators. In an effort to improve the quality of education, the Ministry of Education, Culture, Research and Technology encourages education units and educators to learn and share with each other through learning communities supported by the Merdeka Mengajar Platform (PMM) and various other resources. Learning communities are considered as a strategy to increase competency for teaching staff. This research is to examine the role of the principal's assistance in improving the quality of learning through learning communities at SDN Kalongan 01. The author will use descriptive research methods through a qualitative approach. The data collection technique was carried out using triangulation (observation, interviews and documentation).